(untitled) (Impetus, 2024)
Throughout time, assessment has been considered one of the most difficult topics to address in the educational system due to all that it implies, including the power granted to the teacher over the student. In this sense, pre-service teacher education (PSTE) becomes an important element for the development of competencies necessary for the future teacher, since it advances from a teacher and student-centered posture. Many studies demonstrate the importance of experiencing formative assessment processes in the PSTE, however, in our context this issue is still incipient. The objective of this research was to recognize the assessment experience during the PSTE in the Physical Education degree program at the University of Antioquia. The methodology used was qualitative, specifically the case study. The main strategy for the collection of information was the semi-structured interview. Three main categories emerged as results: assessment as a grade, where the teacher continues being the main protagonist of the assessment and uses traditional methods such as final assignments, midterm exams and exams. To a lesser extent, assessment as a process emerged as a second category, where self-assessment and co-assessment were the two most important elements experienced during the evaluation process. Finally, the path through university education allowed the transformation of the concept of assessment to emerge, showing how, through the lived experience, the concept was modified from a traditional view to a more formative one.